The Influence of Digitalization, Automation and Social Media on Information Systems - Syamsudin, Syamsudin; Ali, Hapzi (Siber International Journal of Digital Business (SIJDB), 2024)
The impact of digitalization, automation, and social media on information systems is explored in a scholarly article within the realm of scientific inquiry. The primary aim of this article is to formulate a hypothesis regarding the relationship among variables for subsequent research endeavors. Sources for research include online repositories such as libraries, Google Scholar, Mendeley, and various other academic digital platforms. The methodology employed in the research involves utilizing resources from e-books and freely accessible electronic journals. The results of this article: 1) digitalization has an effect on information system; 2) automation has an effect on information system; and 3) social media has an effect on information system.